Evaluation of Factors Influencing the Operational Performance of Solar-Powered Street Lighting in Selected Areas - Kabunda, Karen; Rajan, Rekha; Jain, Prem; Manyala, Reccab (Clean Energy Technologies, 2025)
Significant investments have been made in solar street lighting due to its cost-effectiveness compared to grid electricity. Some factors affect the performance of solar street lights. The research investigated battery types, switching systems, shading, inclination, and orientation effects on sampled solar street lights. Systematic sampling and selection of street lights were based on the Yamane Taro formula. Data was collected through fieldwork measurements and observations in addition to the use of questionnaires. The Statistical Package for Social Science (SPSS) and Python were used to analyze the data. Results showed that switching mechanisms, charging systems, and battery type significantly influenced the performance of the studied solar street lights. Lithium-ion (Li-ion) and ultra-capacitors (UCs) outperformed lead-acid batteries, keeping the lights on longer by up to 3 hours compared to flooded lead-acid batteries. Some charge controller components, such as regulating capacitors, were faulty and affected the lithium-ion batteries and ultra-capacitors. The failures caused the batteries to overcharge, resulting in swelling and bursting. The majority of the solar street lights were found to be oriented in the northeast, with some facing northwest in roads like Lumumba, Great North, and Mosi-O-Tunya. Solar panels in the northwest along Lumumba Road and Great North Road exhibited an average power output of 89 W, while those oriented in the northeast had an average power output of 84 W.